A review of the linkage between student participation in the International Baccalaureate Continuum and student learning attributes. (August 2016) - Bryant, Darren A; Walker, Allan; Lee, Moosung
Given the rapid growth in the number of students completing the International Baccalaureate (IB) Diploma Programme and the potential for students to be educated entirely through IB programmes, it is important to understand associations between programme participation and cognitive and non-cognitive learning attributes. Through a mixed methods study, this research considers evidence derived from Diploma Programme examinations, a newly designed and validated student questionnaire, and complementary case studies to examine plausible explanations for associations between IB programmes and learning attributes.